Describe the growth curve in Shami goats and provide a non-linear function based on the composition and production of milk to estimate the performance of the kids (Tikrit Journal of Veterinary Science, 2024)
An investigation into the coefficient of determination (R2) was carried out at the Ruminant Research Station of the Agricultural Research Department/Ministry of Agriculture in Abu Ghraib (20 km west of Baghdad), during the production season, on a sample of (50) kids and their mothers (does). The suitability of five asymptotic nonlinear models to describe milk production and composition of shami goats and kidding body weight growth from weaning to 6 months of age has been examined. The results of this study showed there was a positive and significant (P≤0.05) coefficient of regression (b)for kids weaning weight on daily milk production (kg) were (3.419) kg/kg, that is, the weaning weight increases (3.419) kg, and there was a positive and significant (P≤0.05) regression coefficient (b)for kids age of 6 months (kg) on daily milk production (kg) were (3.763) kg/kg. The coefficient of regression (b) of weight increase during weaning and age six months (kg) was found to be significant and positive (P≤0.05) for children in daily production of milk (kg). Protein content and non-fat solids percentage reached 2.264,0.216, and 0.238 and the determination coefficient (R2) 0.13,0.22 and 0.09, respectively. the coefficient of regression of the 6th month's weight on birth weight according to the formula Y^= 12.95+0.162 BWT2 positive and ranged from 0.176 with a determination coefficient was (0.41). The expected birth weights, weaning weight, and 6th months approach to real weights of shami goat kids by applying Logistic Equation and Brody Equation.